Cost-effectiveness of intra-arterial thrombolysis after successful thrombectomy - Albert J Yoo; Charles B L M Majoie; Johannes Kaesmacher; Arturo Renú; Angel Chamorro; Anne-Laure Bocquet; Thomas Barthe; Bart Jeroen Emmer; Victor Durieux (BMJ Surgery, Interventions, & Health Technologies)
Objectives To study the cost-effectiveness of additional intra-arterial thrombolysis (IA lysis) after successful recanalization with endovascular thrombectomy (EVT).Design A cost-effectiveness model was used to estimate both direct medical costs and quality-adjusted life years (QALYs) gained in six European countries (Spain, the Netherlands, Italy, the United Kingdom, France, Germany) and the USA.Setting The model was based on published data from those countries on health economics.Participants Cost of procedure as well as acute, mid-term and long-term care costs were estimated based on expected modified Rankin Scale (mRS) scores as reported in the Chemical Optimization of Cerebral Embolectomy (CHOICE) trial, which reported improved neurological outcomes after adjunctive IA lysis following EVT.Main outcome measures QALYs in the model were calculated by mapping mRS outcomes from the CHOICE trial to EQ-5D utility values from a validated poststroke cohort, projecting these over a 20-year lifetime horizon with 3% annual discounting, assuming health state transitions only after recurrent stroke (always to a worse mRS) and no recurrent stroke risk in the first 90 days.Results IA lysis was found to be a cost-effective option in seven different countries (Spain, the Netherlands, Italy, the United Kingdom, France, Germany and the USA). We found an incremental cost-effectiveness ratio ranging from US$−2350 per QALY gained in Germany to US$9628 per QALY gained in the USA. A cost-effectiveness acceptability curve showed 90% acceptability of IA lysis at the willingness to pay varying between US$10 000 and US$45 000 depending on the country.Conclusions IA lysis after successful EVT was cost-efficient after reperfusion in the seven countries studied. The early termination, small sample and limited power of the CHOICE trial reduce generalizability of our results. Larger trials are needed to confirm cost-effectiveness of IA lysis after successful EVT.